Flood Warning Prediction Using HEC-HMS Software anf GIS at Panchor Area - Nur Izzati Haziqah Mohd Razalee,; Hamidon, Nuramidah (Progress in Engineering Application and Technology, 2024)
Flooding is a serious hazard to people’s lives, infrastructure, and the environment. Flood warning systems that are effective are critical for disaster management and impact mitigation. This research proposes a comprehensive flood warning prediction approach for the Panchor area using the Hydrologic Modelling System (HEC-HMS) software and Geographic Information System (GIS) tools. Using historical data local hydrological characteristics, the HEC-HMS program model and estimates river flow in response to rainfall events. A rainfall-runoff model that accounts for multiple hydrological components is developed and verified.  The flood prediction system incorporates GIS technology to increase forecast accuracy by analysing and visualizing geographical data. The system continuously monitors rainfall data from meteorological stations in the Panchor catchment area, issues early flood warning based on predetermined river discharge and water level thresholds, and sends alerts authorities and communities for immediate evacuation disaster response. The efficacy of the system is determined by comparing projected flood events to historical flood records, as well as assessing the accuracy, lead time, and reliability of the warning signal of the system. Calibration findings, which illustrate simulated and observed flows, determine model accuracy. The Nash-Sutcliffe Efficiency (NFE) of 0.931 suggests a decent fit, while the validation summary findings for Built Environment and Ecosystems Engineering (BEE) reveal improved model performance with a NFE of 0.755. the complexity of the model has a substantial influence on model performance, with calibration guaranteeing accurate representation of real-world scenarios and parameter selection ensuring proper parameterization and enhanced R2 values.